Message Boards Message Boards

0
|
5995 Views
|
4 Replies
|
4 Total Likes
View groups...
Share
Share this post:

Help me to solve the simultaneous equations

Posted 9 years ago

HI I have a simultaneous equation in terms of a, b, c, d. when I try to use NSolve to solve the equation and get the vales of a, b, c, d in terms of p,q,r,s it is just giving empty bracket as an answer. Any one can help me to solve this equation.

NSolve[{a*b + a*c + b*d + c*d == p && 
              a*b + b*c - b*d == q &&  
              a*b + b*c + a*d + c*d == r && 
              a*b + a*c - a*d == s}, 
            {a, b, c, d}]

Thanks in advance.

POSTED BY: Aadhi A
4 Replies
In[3]:= Reduce[{a*b + a*c + b*d + c*d == p && a*b + b*c - b*d == q && 
   a*b + b*c + a*d + c*d == r && a*b + a*c - a*d == s}, {a, b, c, d}, 
 Backsubstitution -> True]

Out[3]= (p == -q + r + s && a != 0 && 
   b == (a^2 + s - Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])/(2 a) && 
   a^2 + s - Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] != 0 && 
   c == (-3 a^4 + 4 a^2 q - 4 a^2 s - s^2 + 
       3 a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
       s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       Sqrt[2] a^2 \[Sqrt](-(1/(
           a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (-a^4 + 
              2 a^2 q - 2 a^2 s - s^2 + 
              a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
              s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + s -
          Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])) && 
   d == -((a^4 + 2 a^2 s + s^2 - 
         a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
         s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
         Sqrt[2] a^2 \[Sqrt](-(1/(
             a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (-a^4 + 
                2 a^2 q - 2 a^2 s - s^2 + 
                a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
                s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + 
           s - Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))) || (p == -q + 
     r + s && a != 0 && 
   b == (a^2 + s - Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])/(2 a) && 
   a^2 + s - Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] != 0 && 
   c == (-3 a^4 + 4 a^2 q - 4 a^2 s - s^2 + 
       3 a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
       s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
       Sqrt[2] a^2 \[Sqrt](-(1/(
           a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (-a^4 + 
              2 a^2 q - 2 a^2 s - s^2 + 
              a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
              s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + s -
          Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])) && 
   d == -((a^4 + 2 a^2 s + s^2 - 
         a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
         s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
         Sqrt[2] a^2 \[Sqrt](-(1/(
             a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (-a^4 + 
                2 a^2 q - 2 a^2 s - s^2 + 
                a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
                s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + 
           s - Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))) || (p == -q + 
     r + s && a != 0 && 
   b == (a^2 + s + Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])/(2 a) && 
   a^2 + s + Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] != 0 && 
   c == (-3 a^4 + 4 a^2 q - 4 a^2 s - s^2 - 
       3 a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       Sqrt[2] a^2 \[Sqrt]((1/(
          a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (a^4 - 
             2 a^2 q + 2 a^2 s + s^2 + 
             a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
             s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + s + 
         Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])) && 
   d == (-a^4 - 2 a^2 s - s^2 - 
       a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       Sqrt[2] a^2 \[Sqrt]((1/(
          a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (a^4 - 
             2 a^2 q + 2 a^2 s + s^2 + 
             a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
             s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + s + 
         Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2]))) || (p == -q + r + s &&
    a != 0 && 
   b == (a^2 + s + Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])/(2 a) && 
   a^2 + s + Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] != 0 && 
   c == (-3 a^4 + 4 a^2 q - 4 a^2 s - s^2 - 
       3 a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
       Sqrt[2] a^2 \[Sqrt]((1/(
          a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (a^4 - 
             2 a^2 q + 2 a^2 s + s^2 + 
             a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
             s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + s + 
         Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])) && 
   d == (-a^4 - 2 a^2 s - s^2 - 
       a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] - 
       s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
       Sqrt[2] a^2 \[Sqrt]((1/(
          a^4))(a^4 - 4 a^2 q + 4 a^2 r + 2 a^2 s + s^2) (a^4 - 
             2 a^2 q + 2 a^2 s + s^2 + 
             a^2 Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2] + 
             s Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2])))/(2 a (a^2 + s + 
         Sqrt[a^4 - 4 a^2 q + 2 a^2 s + s^2]))) || (s == 0 && 
   p == -q + r && a == 0 && b != 0 && 
   c == (-b^2 + q - Sqrt[b^4 - 2 b^2 q + q^2 + 4 b^2 r])/(2 b) && 
   d == (-b^2 - q - Sqrt[b^4 - 2 b^2 q + q^2 + 4 b^2 r])/(
    2 b)) || (s == 0 && p == -q + r && a == 0 && b != 0 && 
   c == (-b^2 + q + Sqrt[b^4 - 2 b^2 q + q^2 + 4 b^2 r])/(2 b) && 
   d == (-b^2 - q + Sqrt[b^4 - 2 b^2 q + q^2 + 4 b^2 r])/(
    2 b)) || (q == 0 && p == r + s && b == 0 && a != 0 && 
   c == (-a^2 + s - Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2])/(
    2 a) && -a^2 + s - Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2] != 0 && 
   d == -((a (a^2 + 2 r + s + Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2]))/(
     a^2 - s + Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2]))) || (q == 0 && 
   p == r + s && b == 0 && a != 0 && 
   c == (-a^2 + s + Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2])/(
    2 a) && -a^2 + s + Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2] != 0 && 
   d == -((a (a^2 + 2 r + s - Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2]))/(
     a^2 - s - Sqrt[a^4 + 4 a^2 r + 2 a^2 s + s^2]))) || (r == -s && 
   q == 0 && p == 0 && b == 0 && c == 0 && a != 0 && 
   d == -(s/a)) || (s == 0 && q == 0 && p == r && a == 0 && b == 0 && 
   c != 0 && d == r/c) || (s == 0 && r == 0 && q == 0 && p == 0 && 
   a == 0 && b == 0 && c == 0)
POSTED BY: Frank Kampas

That means there is no solution. Also since there are nonnumeric parameters, you might as well use Solve because that's what NSolve will have to do anyway.

POSTED BY: Daniel Lichtblau

Possibly solve the equations stepwise. For example

In[49]:= Solve[a*b + a*c + b*d + c*d == p, a]

Out[49]= {{a -> (-b d - c d + p)/(b + c)}}

In[52]:= a = (-b d - c d + p)/(b + c);

Then use this result in second equation for b, etc.

POSTED BY: S M Blinder

together enter image description here

POSTED BY: Simon Cadrin
Reply to this discussion
Community posts can be styled and formatted using the Markdown syntax.
Reply Preview
Attachments
Remove
or Discard

Group Abstract Group Abstract